Development of a Mesoscale Inversion System for Estimating Continental‐Scale CO2 Fluxes. (25th August 2020) - Wesloh, Daniel; Lauvaux, Thomas; Davis, Kenneth J.
Abstract: Computational requirements often impose limitations on the spatial and temporal resolutions of atmospheric CO2 inversions, increasing aggregation and representation errors. This study enables higher spatial and temporal resolution inversions with spatial and temporal error structures similar to those used in other published inversions by representing the prior flux error covariances as a Kronecker product of spatial and temporal covariances and by using spectral methods for the spatial correlations. Compared to existing inversion systems that are forced to degrade the resolution of the problem in order to bring the dimensionality down to computationally tractable levels, this inversion framework is able to take advantage of mesoscale transport simulations and more of the complexity of spatial and temporal covariances in the surface CO2 fluxes. This approach was successfully implemented over one month with an identical‐twin observing system simulation experiment (OSSE) using a set of assumptions about the prior flux uncertainties compatible both with continental‐scale uncertainty estimates and with comparisons of vegetation models to flux towers. The demonstration illustrates the potential of the newly developed inversion system to use high‐temporal‐resolution information from the North American tower network, to extract high‐resolution information about CO2 fluxes that is inaccessible to coarser resolution inversion systems, and to simultaneously optimize an ensemble of prior estimates. This demonstration sets the stage for regional flux inversions that can take full advantage of the high‐resolution data available in tower CO2 records and mesoscale atmospheric transport reanalyses, include more realistic prior error structures, and explore specifying prior fluxes with ensembles. Plain Language Summary: This paper describes a new inverse framework for deriving surface carbon dioxide (CO2 ) fluxes at high spatial and temporal resolutions from atmospheric mole fraction measurements. We demonstrate the potential of the system over North America by inverting for subdaily biogenic CO2 fluxes while accounting for the complexity of spatio‐temporal structures in flux error covariances in a data‐based manner. Key Points: A new inversion system uses spectral methods for spatial correlations to do a 27 km subdaily inversion over North America The software package allows simultaneous optimization of multiple prior mean flux estimates The system is demonstrated over continental North America for a network of seven towers